2013
DOI: 10.1186/1471-2458-13-25
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an employee wellness programme in clothing/textile manufacturing companies: a randomised controlled trial

Abstract: BackgroundThe prevalence of health risk behaviours is growing amongst South African employees. Health risk behaviours have been identified as a major contributor to reduced health related quality of life (HRQoL) and the increased prevalence of non-communicable diseases. Worksite wellness programmes promise to promote behaviour changes amongst employees and to improve their HRQoL. The aim of this study was to evaluate the short-term effects of an employee wellness programme on HRQoL, health behaviour change, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 29 publications
(28 reference statements)
0
53
1
2
Order By: Relevance
“…Few trials have specifically targeted adult men (George et al, 2012) or adults in developing countries like South Africa that are undergoing a health transition involving markedly increased NCD-mortality rates, especially among men (Cecchini et al, 2010; Mayosi et al, 2009; Mayosi et al, 2012). One of the few randomized controlled trials (RCTs) of a health-promotion intervention in South Africa found that the intervention did not increase physical activity compared with a control group (Edries et al, 2013). …”
mentioning
confidence: 99%
“…Few trials have specifically targeted adult men (George et al, 2012) or adults in developing countries like South Africa that are undergoing a health transition involving markedly increased NCD-mortality rates, especially among men (Cecchini et al, 2010; Mayosi et al, 2009; Mayosi et al, 2012). One of the few randomized controlled trials (RCTs) of a health-promotion intervention in South Africa found that the intervention did not increase physical activity compared with a control group (Edries et al, 2013). …”
mentioning
confidence: 99%
“…Su principal desventaja es que no describe la importancia de cada factor dándole mayor énfasis al ámbito biológico e individual que a lo social. Este es el modelo que predomina encontrado en 17 investigaciones [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27].…”
Section: Resultsunclassified
“…A recent RCT found that a worksite-wellness intervention did not increase self-reported physical activity, but the sample was small, 90% of participants were women, and the follow-up was brief, only six weeks post-intervention (Edries et al, 2013). Although a RCT found that an intervention increased self-reported physical activity in young South African adolescents (Jemmott et al, 2011), the current study is, to our knowledge, the first to demonstrate that a theory-based behavioral intervention can significantly increase self-reported physical activity among men in sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been numerous calls for interventions to increase physical activity among South Africans (Cecchini et al, 2010; Joubert et al, 2007; Mayosi et al, 2009; Mayosi et al, 2012; Pillay et al, 2012; Skaal and Pengpid, 2011; Temple, 2007), to our knowledge, only two RCTs testing physical-activity interventions in South Africa have been published. One focused on young adolescents (Jemmott et al, 2011); 90% of participants in the other were women (Edries et al, 2013). Besides physical inactivity, a high prevalence of other modifiable risk factors for NCDs, including high fat intake (Bourne et al, 2002), insufficient fruit-and-vegetable consumption (World Health Organization, 2013), and obesity (World Health Organization, 2011) has been documented among South Africans.…”
mentioning
confidence: 99%